Mathematics Learning Process Through Game-Based Methods: A Pedagogical Content Knowledge Perspective - Reni Nuraeni; Al Jupri; Elah Nurlaelah (Universitas Wiralodra, 2025)
Pedagogical Content Knowledge (PCK) is an essential competency for mathematics teachers, as it significantly influences the effectiveness of student learning. This study examines the implementation of game-based learning in mathematics instruction through the lens of PCK. The research was conducted through observations of a junior high school mathematics teacher in Bandung Regency. The primary objective of this study is to analyze the mathematics learning process using the game-based method, focusing on its alignment with PCK principles. Data were collected through classroom observations and unstructured interviews with both teachers and students. A qualitative descriptive approach was employed for data analysis. The findings reveal the following key points: (1) Teachers do not prepare lesson plans or teaching modules before conducting classroom instruction; (2) Teachers' content knowledge requires reinforcement; (3) The formulation of exercises remains simplistic, lacking a range of difficulty levels (easy, medium, difficult), and does not include higher-order thinking skills (HOTS) questions; and (4) There is insufficient reinforcement when students struggle to recall fundamental concepts, such as fractions.